Acute otitis media and pneumococcal vaccination – an observational cross-sectional study of otitis media among vaccinated and unvaccinated children in Greenland. Issue 1 (1st January 2021) - Jespersen, Simon Imer; Demant, Malene Nøhr; Pedersen, Michael Lynge; Homøe, Preben
ABSTRACT: Streptococcus pneumoniae is one of the main pathogens leading to otitis media. In 2010, the 13-valent pneumococcal conjugate vaccine (PCV13) was implemented in the Greenlandic childhood vaccination programme, but the effect of this change is not yet well documented. The objective of this study is to evaluate the effect of the implementation based on the number of episodes of acute otitis media (AOM). Data are obtained from medical records. We included all children born from 1 January 2015 to 30 September 2016, and thus eligible for the three doses of PCV13 including one year of follow-up time. Exclusion criteria were uncertain vaccination status and predefined comorbidities. The children were divided into two groups based on vaccination status: "Vaccinated" or "Incomplete/delayed". We included 1077 children in total, 742 children were allocated to the "Vaccinated" group and 335 children were allocated to the "Incomplete/delayed" group. There were significantly fewer episodes of AOM in the "Incomplete/delayed" group (p = 0.01). In conclusion Greenlandic children completely and timely vaccinated with PCV13 and born between January 2015 and September 2016 did not have fewer episodes of AOM compared to children who had incomplete or delayed vaccination status. Abbreviations : PCV13: 13-valent pneumococcal conjugate vaccine; OM: otitis media; AOM: acute otitis media; CSOM: chronic suppurative otitis media; WHO: World Health Organisation; NTHi: nontypeable Haemophilus influenzae